Regulation of ionic current through a surround-gated nanopore via field effect control - Pariya Sornmek; Darinee Phromyothin; Jakrapong Supadech; Kittipong Tantisantisom; Thitikorn Boonkoom (Physical Chemistry Chemical Physics, 2022)
Ability to control ionic current flowing through a nanopore has been demonstrated using the electric field effect on an electrical gate surrounding the nanopore. The gate electrode was introduced onto a single nanopore by depositing an Au layer on a silicon nitride diaphragm prior to pore milling using a focused ion beam technique. A hafnium oxide layer was subsequently deposited onto the nanopore structure as an insulating layer to protect the gate electrode. The device operation was investigated in KCl electrolyte and the ionic current regulating ability was examined under the influence of the gate voltage and the nanopore size. It was found that the device shows significant ionic current response with respect to the applied gate voltage. The resulting electric field dependent behavior of the fabricated nanopore suggests that the ionic current is influenced by positive surface charge inside the nanopore. The gate influence was more pronounced in the smaller nanopore and with higher source-drain voltage. The gate and pore size dependence behavior allows the potential to regulate ionic current as a nanoscale valve in nanochannel applications.
Keywords: Nanopore and Nanochannel Transport Studies; Fuel Cells and Related Materials; Membrane-based Ion Separation Techniques